2008
DOI: 10.1007/s11099-008-0031-y
|View full text |Cite
|
Sign up to set email alerts
|

Changes in photosynthetic capacity and antioxidant enzymatic systems in micropropagated Zingiber officinale plantlets during their acclimation

Abstract: Ginger (Zingiber officinale Rosc.) plantlets were propagated in vitro and acclimated under different photosynthetic photon flux densities (60 and 250 μmol m -2 s -1 = LI and HI, respectively). Increases in chlorophyll (Chl) content and Chl a/b ratio were found under both irradiances. In vitro plantlets (day 0) exhibited a low photosynthesis, but chloroplasts from in vitro leaves contained well developed grana and osmiophillic globules. Photoinhibition in leaves formed in vitro was characterized by decrease of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…In Solanum tuberosum (Baroja et al 1995), Spathiphyllum floribundum (Van Huylenbroeck and Debergh 1996), Rehmania glutinosa (Seon et al 2000), Capsicum annuum (Estrada-Luna et al 2001), Ocimum basilicum (Siddique and Anis 2008) and Zingiber officinale (Guan et al 2008) P N also decreased in the first days after transplantation and increased thereafter. In present experiments we measured persistent leaves, however, significant increase in P N to values higher than during in vitro growth was usually found only when new leaves were fully developed (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Solanum tuberosum (Baroja et al 1995), Spathiphyllum floribundum (Van Huylenbroeck and Debergh 1996), Rehmania glutinosa (Seon et al 2000), Capsicum annuum (Estrada-Luna et al 2001), Ocimum basilicum (Siddique and Anis 2008) and Zingiber officinale (Guan et al 2008) P N also decreased in the first days after transplantation and increased thereafter. In present experiments we measured persistent leaves, however, significant increase in P N to values higher than during in vitro growth was usually found only when new leaves were fully developed (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Exposure of Calathea louisae and Spathiphyllum floribundum plantlets to high irradiance immediately after transplantation caused photoinhibition and even Chl photobleaching (Van Huylenbroeck 1994, Van Huylenbroeck et al 1995 but no photoinhibition was observed in plants acclimatized under low irradiance (Van Huylenbroeck 1994). Similarly, photoinhibition characterized by decrease in variable to maximum fluorescence ratio (F v /F m ) was observed in Rosa hybrida and Zingiber officinale plantlets in the first week after ex vitro transfer (Sallanon et al 1998, Genoud et al 1999, Guan et al 2008. Immediately after ex vitro transfer, reversible photoinhibition was observed in Castanea sativa and Vitis vinifera (Carvalho et al 2001).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Based on several reports (Rout et al, 2001, Guo and Zhang, 2005, Ma and Gang, 2006, Guo et al, 2007, Guan et al, 2008and Zheng et al, 2008 ginger, is constrained severely can summarized as following: (1) ginger normally propagates by its rhizome, with a low proliferation rate, and the reproducing part (the rhizome) is also the economically used part of the ginger plant, which restricts the availability of ginger seeds needed for cultivation, (2) easily infected by soil-born pathogens such as bacterial wilt (Pseudomonas solanacearum), soft rot (Pythium aphanidermatum), and nematodes (Meloidogyne spp. ), which cause heavy losses in yield.…”
Section: Introductionmentioning
confidence: 99%
“…P N was higher in plants grown under HI than under LI. In several plant species, P N also decreased during the first days after transplantation and increased thereafter but significant increase in P N to values higher than during in vitro growth was usually found only when new leaves were fully developed (see review , and recent papers Siddique and Anis 2008, Guan et al 2008). No statistically significant effect of ABA was found in plantlets grown in vitro and also 1 d after ex vitro transfer while 7 d after ex vitro transfer P N was lower in ABA-treated plants than in control plants (Fig.…”
Section: Resultsmentioning
confidence: 99%